PELATIHAN PENGEMBANGAN MEDIA PEMBELAJARAN DIGITAL UNTUK MENDUKUNG PERAN GURU DALAM PENYAMPAIAN MATERI DI KELAS - Diva Apri Mulya; Muhammad Ali Imron; Egi Agustandi; Helmi Syarif; Shobrina Fitri; Ade Taufan; Muhammad Rizzky Abdillah (Hira Institute, 2025)
This community service program aims to improve teachers' skills in developing and utilizing digital learning media to support their role in delivering learning materials. The activity was conducted at Sungai Tutung 02/III Public Elementary School, targeting all 17 elementary school teachers. The activity employed a workshop approach in the form of in-service training with a participatory approach, where participants actively engaged through hands-on practice in creating digital-based learning media using the Genially application. The activity included an introduction to digital learning media, training in media creation, and mentoring for classroom implementation. The results of the activity demonstrated an increase in teachers' understanding and skills in designing creative and interactive digital learning media. Teachers demonstrated high enthusiasm and were able to produce Genially-based learning media that could be used in the learning process. This activity had a positive impact on learning innovation and is expected to increase student motivation and understanding of the material presented.